Purification of proteins on newly synthesized DNA using iPOND - Dungrawala, Huzefa (Methods Mol Biol, 2015)
The replisome is a large protein machine containing multiple enzymatic activities needed to complete DNA replication. In addition to helicase and polymerases needed for copying the DNA, the replisome also contains proteins like DNA methyltransferases, histone chaperone and chromatin modifying enzymes to couple DNA replication with chromatin deposition and establishment of the epigenetic code. In addition, since template DNA strands often contain DNA damage or other roadblocks to the replication machinery, replication stress response proteins associate with the replisome to stabilize, repair and restart stalled replication forks. Hundreds of proteins are needed to accomplish these tasks. Identifying these proteins, monitoring their post-translational modifications, and understanding how their activities are coordinated is essential to understand how the genome and epigenome are duplicated rapidly, completely, and accurately every cell division cycle. Here we describe an updated iPOND (isolation of proteins on nascent DNA) method to facilitate these analyses.